Internships and engineering: beliefs and behaviors of academics. Issue 6 (8th July 2019) - Matusovich, Holly; Carrico, Cheryl; Harris, Angela; Sheppard, Sheri; Brunhaver, Samantha; Streveler, Ruth; McGlothlin Lester, Marlena B.
Abstract : Purpose: Internships play an important role in the choices engineering students make about future career pathways though there is little research about the messaging students receive regarding internships from academics. This messaging is important because it can contribute to the expectations students set for internships which in turn influences the interpretation of the experience and sense of appropriateness of that particular career pathway. Situated in Expectancy X Value theory, the purpose of this paper is to examine the beliefs and behaviors of the academics with whom engineering students interact as related to internship experiences. Design/methodology/approach: The authors conducted and analyzed interviews with 13 career center employees and 14 academic advisers/faculty members across six demographically and geographically diverse schools. Interviews were coded, and within and across case patterns developed. Findings: Across all six schools, interview participants believe internships are important for students with regard to three areas: enabling career discovery, providing opportunities for development of career skills and helping students with full-time job acquisition. However, participants describe few direct actions associated with these beliefs. The lack of recommended actions for making the most of the internship experience, despite a strong belief in their importance, is a major finding of this paper. Originality/value: This study is original in that it examines an important perspective that is not often a focus of research related to internships: academic advisors, faculty or career center personnel. The multi-institution sample enhances the value of the study as commonalities were seen despite variation in schools, enabling recommendations useful to a variety of contexts.